Corporate Governance in India - Dawar, Neha (Digital Repository of Theses, 2025)
Due to widespread corporate scandals and failures around the world, there has been a renewed interest in the effect of corporate governance on firm performance. The majority of research concerning corporate governance and its effect on firm performance has been undertaken in developed countries and markets, particularly the UK and the US, but relatively little evidence is provided in the Middle East, specifically INDIA. This study investigates the effect of the corporate governance on firm performance of the Indian industrial and services companies during the period in Period 2020 to 2020 and 2021 to 2023. This study primarily employs the agency theory to investigate the relationship between corporate governance and firm performance. The agency theory is concerned with the agency problem between principals and agents (i.e. shareholders and managers, respectively), which undermines value maximization. It has been argued that the board of directors, ownership concentration and managerial ownership are efficient corporate governance mechanisms to solve the agency problem between shareholders and management.